The New York State Safe Motherhood Initiative: Early Impact of Obstetric Hemorrhage Bundle Implementation - Goffman, Dena; Ananth, Cande V.; Fleischer, Adiel; D'Alton, Mary; Lavery, Jessica A.; Smiley, Richard; Zielinski, Kristin; Chazotte, Cynthia; for the Safe Motherhood Initiative Obstetric Hemorrhage Work Group (American Journal of Perinatology, 2019)
Objective To determine the effects of the Safe Motherhood Initiative's (SMI) obstetric hemorrhage bundle in New York State (NYS).Study Design In 2013, the SMI convened interprofessional workgroups on hemorrhage, venous thromboembolism, and hypertension tasked with developing evidence-based care bundles. Participating hospitals submitted data measured before, during, and after implementation of the hemorrhage bundle: maternal mortality, intensive care unit (ICU) admission, cardiovascular collapse, hysterectomy, and transfusion of ≥4 units of red blood cells (RBCs). Data were analyzed for trends stratified by implementation status.Results Of the 123 maternity hospitals in NYS, 117 participated, of which 113 submitted data. Of 250,719 births, transfusion of ≥4 units RBCs (1.8 per 1,000) and ICU admissions (1.1 per 1,000) were the most common morbidities. Four hemorrhage-related maternal deaths (1.6 per 100,000) and 10 cases of cardiovascular collapse requiring cardiopulmonary resuscitation (4.0 per 100,000) occurred. Hemorrhage morbidity did not change over the five quarters studied. Risks were similar across hospital level of care and implementation status.Conclusion Statewide implementation of bundles is feasible with resources critical to success. The low hemorrhage-related maternal death rate makes changes in mortality risk difficult to detect over short time intervals. Long-term and timely data collection with individual expert case review will be required.
Keywords: safe motherhood initiative; obstetric hemorrhage; maternal mortality